AB0828 Comparing Synovial Fluids and Inflammatory Markers during Acute Pseudogout in Patients with and without Known Inflammatory Arthropathy. (10th June 2014) - Alhaddad, B.; Ballou, S.; Aponte, J.
Abstract : Background: It is known that the presence of uric acid or calcium pyrophosphate (CPPD) crystals in synovial joints can activate the inflammasome and release interleukin-1 (1) promoting an acute attack of arthritis; sometimes associated with severe systemic symptoms and even pseudo-meningitis picture (2, 3). It is not clear whether having an underlying cytokine release from inflammatory arthritis would produce a synergetic effect and result in more intense inflammation during pseudogout flare. Objectives: Our clinical observations have suggested that pseudogout may be more dramatic with a greater inflammatory response in patients who have underling inflammatory arthropathy compared to those without. To our knowledge; no published study has compared the severity of inflammation associated with pseudogout in these two groups. Methods: We analyzed data from 62 patients who had laboratory confirmation of CPPD crystals in synovial fluid analysis over 3 years (2008 through 2010). Patients were categorized into 2 groups according to the presence (Group 1) or absence (Group 2) of an underlying inflammatory arthropathy. The data compared included CRP, ESR, WBC and neutrophil percentage in serum and synovial fluids. For clinical comparison we looked into the number of involved joints in each group. Presence of fever and degree of joint inflammation could not be detected. Results: Among 62 patients, 28 were found to have an underlying inflammatory arthropathy. Male to female ratio was 1:1. The inflammatory arthropathies were as follow: Known history of gout (N=21), Rheumatoid Arthritis (N=8), Systemic Lupus Erythematosus (N=2) and IBD related arthritis (N=1). The mean age for group 1 in years was 72.4 vs 78.7 in group 2. 43% of patients in group 1 were below the age of 70 and 10% were below 50 compared to 14% and 0% respectively in the other group. There was not enough power to compare the number of involved joints but group 1 had more tendency towards having 2 or more involved joints (28 vs 9%). the mean CRP was higher in group 1: 14.6 [3.95, 20.95] mg/dL vs 8.9 [2.6, 20.4] mg/dL; but that was not statistically significant (p=0.51). There was no difference in WBC elevation in serum or synovial fluids between the groups. The only factor that showed a statistically significant difference was the serum neutrophil percentage, (79 [72.6, 82] vs. 71.85 [62.75, 77.9) P=0.043; which was not considered clinically meaningful. Conclusions: We noticed a trend towards a higher CRP and higher number of involved joints with pseudogout attacks in patients with underlying inflammatory arthropathy compared to those without. Our observation suggests that the presence of underlying inflammation in joints may predispose to pseudogout at an earlier age then expected. Further studies are needed to better understand the behavior of pseudogout in patients with other established rheumatologic diagnosis. References: Winzer M, Tausche AK, Aringer M. Crystal-induced activation of the inflammasome: gout and pseudogout. Z Rheumatol. 2009 Nov;68(9):733-9. Geraldine McCarthy. Primer on the Rheumatologic diseases, 2008:263 to 270 Sekijima Y, Yoshida T. CPPD crstal deposition disease of the cervical spine, a common cause of acute neck pain encountered in the neurology department. J Neurol Sci. 2010 Sep 15, 296(1-2):79-82. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3763